The living Bauhaus. Tel Aviv experience - Salmin, Leonid (project baikal, 2026)
The article is devoted to the modernist heritage in the architecture of Tel Aviv, and, above all, the influence of representatives of the Bauhaus school on the development of the city. The article examines the specifics of the development that took place from the founding of the city in 1925 until the 1950s, as well as the features of architectural and urban planning concepts that determined the stylistic and functional continuity in the urban history of Tel Aviv.
Keywords: Tel Aviv; Bauhaus; White City; modernism; functionalism; urban planning; urban environment; urbanism